Estrategias de marketing digital en la Empresa Comercial “Depósito Hermanos Renjifo Mancilla” de la ciudad de Babahoyo, periodo 2023. - Tobar Renjifo, Alexis Enrique (2024)
This case study, which was carried out in the company "Deposito hermanos Renjifo Mancilla" in the city of Babahoyo, period 2023, uses a mixed approach and as a descriptive, analytical and inductive methodology, examining the digital marketing strategies that the company uses on social networks to attract customers, determining new potential strategies to obtain a better result in its income and positioning. Through the survey and interview, shortcomings were identified that prevent the company from boosting its number of sales. Likewise, the findings highlight the importance of persuasive audiovisual content and the strategic use of social networks. This study not only reveals relevant information for the company, but also provides practical recommendations for the company "Deposito Hermanos Renjifo Mancilla" to improve its marketing situation and in this way, it can attract a greater number of customers and increase its revenue. The conclusions and recommendations offer valuable guidance for the company to be known and obtain better performance.